PENGARUH PENAMBAHAN SASOBIT PADA WARM MIX ASPHALT TERHADAP MUTU CAMPURAN BERASPAL - Eka Hadi Purwanto; Hartomo Sandi Sakti; Bagus Hario Setiadji; Supriyono Supriyono (Jurnal Karya Teknik Sipil, 2014)
Warm mix asphalt technology have possibility to makes, spreading, and compress in lower temperature than hot mix asphalt. This technology used with add the additive material named Sasobit. Because of that we did the research about mixing asphalt with Asphalt Institute methode. The asphalt degree is 4,5%, 5%, 5,5%, 6%, dan 6,5% add into Sasobit 0%, 2%, 3%, and 4% to establish mixing and solid temperature in the mix. This research compared the quality between mixing asphalt with Sasobit and mix without Sasobit as a control. Result of this research showed that decrease temperatur because of increment Sasobit 2% reduce until 6˚C, increment Sasobit 3% reduce until 7,5%, dan increment Sasobit 4% reduce until 7,8%. The other benefit from adding the Sasobit into mix asphalt is increase stability value, decrease presentage degree of utilizing asphalt, and decrease the gas emision from mixing asphalt. However, mixing with add Sasobit have lack, where the mix become more stiff and hard so that the asphalt is easier to be damage if compared with mix without Sasobit.